La Didáctica en el proceso de enseñanza – aprendizaje de Lengua y Literatura en la “Unidad Educativa 11 de Noviembre, en los novenos años”. - Yánez Yánez, María Augusta (2022)
The methodological strategies in the teaching-learning process from Language and Literature area, are the main factor due to, their used allows to motive students in the assimilation of knowledge; So that, the research has as aim to describe the methodological strategies that influence in the teaching-learning process from Language and Literature area in Unidad Educativa 11 de Noviembre. Answers the problem: ¿What are the methodological strategies that influence the teaching-learning process of Language and Literature in Unidad Educativa 11 de Noviembre ? The quantitative methodology was applied: The survey was used as a technique and the questionnaire as a data collection instrument Deductive method. The results show that teachers don’t know about active methodologies, that let the development of oral and written communication in Language and Literature subject, the strategies that teachers use, are the traditionalist ones, where the student receives information and doesn’t build their own knowledge, That’s why, students can’t develop the assertive communication competence, So students need to improve speaking ability in front of an audience, in order to express coherent ideas and being able to identify main and secondary ideas in a text; be analytical and reflective people, who can give their points of view. This one allows to elaborate the design “Methodological Strategies Guide in the teaching-learning process in the development of Language and Culture, Oral Communication, Writing and Reading in the Language and Literature area”. The application of the guide demonstrates a significant change; Getting that students participate actively; correct pronunciation in their oral expression and being able to build their own ideas.